EFECTOS DEL SORBATO DE POTASIO A DIFERENTES CONCENTRACIONES y TIEmPO DE ExPOSICIóN SOBRE EL CICLO CELULAR y EL mATERIAL GENÉTICO EN mERISTEmOS RADICULARES DE AllIuM CEPA l. (CEBOLLA) - Quispe y Cols., Joselyne (2019)
In order to determine the effect of Potassium Sorbate on the cell cycle in root meristems of Allium cepa L. “onion” set three experimental groups were exposed to solutions of Potassium Sorbate at concentrations of 0.5, 1 and 2g /l, for 6, 7 and 8 hours each and a control group. Later the respective color in 2% Acetic orcein according to the technique of Tjio and Levan, observed with the compound microscope a total of 1500 meristematic cells in each of the treatments. The appropriate treatment results after 8 hours of exposure to the concentration of 2 g / L showed a decrease in mitotic index of 11.26%, while it increased the rate at 95.57% prophasic index. There were also alterations as chromosome breaks, anaphasic bridges and binucleated cells. The tests and analysis of variance showed significant differences between the different treatments, as confirmed by multiple comparison test of Duncan averages. It shows a probable genotoxic effect in the genetic material by Potassium Sorbate and an alteration in the cell cycle of meristems of A. cepa L., likewise, is found biosensor function of A. cepa L. in the study of substances that may affect the cell cycle.